Combination of butafosfan associated with cyanocobalamin to increase fertility in female zebu (Research, Society and Development, 2020)
The aim of the present study was to evaluate the effect of injectable vitamin mineral supplementation with phosphorus and vitamin B12 on the reproductive performance of Nellore bovine females raised in the state of Pará, submitted to the TAI protocol. 170 cows distributed in 2 treatments were used, T1 (n = 93) receiving 10 ml of injectable supplementation and T2 (n = 77) receiving 10 ml of placebo, all in the D0 of the IATF protocol. All cows received the same TAI protocol in which: D0 (intravaginal P4 + 2 mg BE implant IM), D8 (0.5 mg PGF2α + 300 UI eCG + 1 mg EC all IM and removal of the implant P4), D10 (IATF) and D40 (Gestational diagnosis with ultrasound). The data were tabulated in Microsoft Excel spreadsheets and analyzed using the Statistical Analysis System [SAS] (2009) and submitted to analysis of variance by the 7 Proc GLMMIX. The pregnancy rate at T1 was 61.29% (57/93) and T2 at 45.45% (35/77) with a significant difference (P